Penyelamat tanah, air, dan lingkungan - Arsyad, Sitanala; Rustiadi, Ernan (Jakarta : Crestpent Press, 2008)
Issues of environmental and natural resources management.
Includes bibliographical references and index.
Keywords: Environmental management -- Indonesia; Natural resources -- Management